A case of giant cell osteosarcoma in a Scottish fold cat - Dayı, B; Mutlu, AM; Akkoç, A; Sevimli, A (Journal of the Hellenic Veterinary Medical Society, 2023)
This study describes a case of giant cell osteosarcoma (GCO) localised on the right scapulae in a six-year-old neutered male Scottish Fold cat. GCO is a rare tumour in domestic animals. This tumour is also known as giant cell-rich osteosarcoma. Multinucleated giant cells and osteoid structures are observed in GCO. The mass was 4.6 x 4.4 x 4.3 cm in size and very firm. Microscopically, fusiform spindle-shaped cells and multinucleated giant cells were observed. There were 4-8 mitotic figures in three random high-power fields (400x). Osteoid structures and necrosis were detected in several areas. In these areas, atypia was observed in the cells. Immunohistochemically, vimentin expression was observed in neoplastic cells and multinucleated giant cells. No immunoreactivity against actin and cytokeratin was observed in neoplastic cells. Additionally, vimentin expression was detected in the periphery of blood vessels and actin expression in blood vessel smooth muscle cells. As a result of histopathological and immunohistochemical findings, the mass was determined to be GCO.